Relationship between Ethical Leadership and Sustainability in Small Businesses - Amisano, David Christopher; Anthony, Peter (Journal of Leadership, Accountability and Ethics, 2017)
Since the 2008 financial crisis, business leaders have faced uncertainty regarding the impact of ethical leadership behaviors. Because small business leadership involves multiple facets of behavior and decision-making, small business leaders may have an insufficient understanding of the impact of ethical leadership behaviors on sustainability. The purpose of this study was to examine the relationship between ethical leadership and financial, social, and environmental sustainability in small businesses. The participants were 80 members of a Miami, Florida chamber of commerce. Correlation analysis and Bonferroni corrected calculation indicated significant relationships (p < .001) between ethical leadership behaviors and social and environmental sustainability